1987
DOI: 10.1111/j.1768-322x.1987.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulation upon post‐hatching development of fibre types in normally innervated fast and slow latissimus dorsii muscles of the chicken

Abstract: In chicken, the main characteristic properties of muscle fibre types in slow anterior (ALD) and fast posterior (PLD) latissimus dorsii are acquired during post-hatching development. At day 4 it becomes possible to distinguish between alpha' and beta' fibre types in ALD muscle. At the same time, mATPase staining and NADH-TR activity permit recognition of alpha w and alpha R fibres within PLD muscle. During further development, muscle fibre typology progressively changes towards the adult slow and fast type. Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In broiler chickens, Khaskiye et al . () also observed an increase in the physical muscle characteristics (such as weight and diameter) and modulation of its fibers due to exercise. They also verified that the pattern of physical activity influences the intensity of muscle differentiation, and that both the placement of barriers and ramps in conventional boxes are crucial for obtaining heavier muscles.…”
Section: Resultsmentioning
confidence: 82%
“…In broiler chickens, Khaskiye et al . () also observed an increase in the physical muscle characteristics (such as weight and diameter) and modulation of its fibers due to exercise. They also verified that the pattern of physical activity influences the intensity of muscle differentiation, and that both the placement of barriers and ramps in conventional boxes are crucial for obtaining heavier muscles.…”
Section: Resultsmentioning
confidence: 82%
“…This phenomenon is significant for determination of fiber types affected by myoblast differentiation caused by in vivo microenvironment differences during muscle fiber regeneration after injury or atrophy. Moreover, low frequency electrical stimulation increased oxidative activity in all muscle fiber types, whereas high-frequency stimulation resulted in decreased oxidative activity ( Khaskiye et al, 1987 ).Therefore, the muscle fiber types of normally innervated chicks changed with different electrical stimulation frequencies, indirectly proving that the activity pattern of the birds affected the difference between slow and fast muscle fiber types.…”
Section: Regulating Factors Of Muscle Fiber Heterogeneitymentioning
confidence: 99%
“…There are also indications that certain forms of mechanical overload (stress, exercise, compensatory hypertrophy) may promote an increase in the number of m al animal species (Kelley, 1996). In broiler chickens, Khaskiye et al (1987) observed an increase in the physical muscle characteristics (such as weight and diameter) and modulation of its fibers due to the exercise. The authors also verified that the pattern of physical activity influences the intensity of muscle m , s la rowth rates and reared with or without outdoor access.…”
Section: Genetic Factorsmentioning
confidence: 99%